Temporal and Spatial Epigenome Editing Allows Precise Gene Regulation in Mammalian Cells. Issue 1 (4th January 2019) - Kuscu, Cem; Mammeadov, Rashad; Czikora, Agnes; Unlu, Hayrunnisa; Tufan, Turan; Fischer, Natasha Lopes; Arslan, Sevki; Bekiranov, Stefan; Kanemaki, Masato; Adli, Mazhar
Abstract: Cell-type specific gene expression programs are tightly linked to epigenetic modifications on DNA and histone proteins. Here, we used a novel CRISPR-based epigenome editing approach to control gene expression spatially and temporally. We show that targeting dCas9–p300 complex to distal non-regulatory genomic regions reprograms the chromatin state of these regions into enhancer-like elements. Notably, through controlling the spatial distance of these induced enhancers (i-Enhancer) to the promoter, the gene expression amplitude can be tightly regulated. To better control the temporal persistence of induced gene expression, we integrated the auxin-inducible degron technology with CRISPR tools. This approach allows rapid depletion of the dCas9-fused epigenome modifier complex from the target site and enables temporal control over gene expression regulation. Using this tool, we investigated the temporal persistence of a locally edited epigenetic mark and its functional consequences. The tools and approaches presented here will allow novel insights into the mechanism of epigenetic memory and gene regulation from distal regulatory sites. Graphical Abstract: Highlights: H3K27 can be acetylated on non-regulatory regions that are epigenetically reprogrammed into enhancer-like elements. This targeting approach results in locus-specific manipulation of epigenetic marks and conformational changes in chromatin structure. Deposited mark has a differential rate of temporal persistence at the i-Enhancer versus the promoter region.